2017
DOI: 10.3168/jds.2017-12773
|View full text |Cite
|
Sign up to set email alerts
|

The effect of source of supplemental dietary calcium and magnesium in the peripartum period, and level of dietary magnesium postpartum, on mineral status, performance, and energy metabolites in multiparous Holstein cows

Abstract: The objective of this study was to determine the effects of feeding different supplemental sources of Ca and Mg in the peripartum period, and different dietary levels of Mg postpartum, on plasma mineral status, performance, and aspects of energy metabolism in transition dairy cows. Multiparous Holstein cows (n = 41) were used in a completely randomized design with a 2 × 2 factorial arrangement of treatments starting at 28 d before expected parturition. Main effects were source assignments (CS = common sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
2
10
2
Order By: Relevance
“…The MgO diets yielded a greater concentration of soluble Mg than the BLN diets, which could favor ruminal absorption of Mg from MgO (Jittakhot et al, 2004;Goff, 2018). This reasoning is in agreement with Leno et al (2017) who found a trend toward lower plasma Mg in cows fed CaMg(CO 3 ) 2 compared with cows fed MgO in diets containing 0.35 to 0.4% Mg, suggesting a similar but possibly lower absorption of Mg from CaMg(CO 3 ) 2 (which is 1 of the 2 components of our BLN treatments). However, this needs to be further evaluated with in vivo experiments where other indicators such as plasma concentration of Mg can be assessed.…”
Section: Ruminal Ph and Mg Solubilitysupporting
confidence: 84%
See 1 more Smart Citation
“…The MgO diets yielded a greater concentration of soluble Mg than the BLN diets, which could favor ruminal absorption of Mg from MgO (Jittakhot et al, 2004;Goff, 2018). This reasoning is in agreement with Leno et al (2017) who found a trend toward lower plasma Mg in cows fed CaMg(CO 3 ) 2 compared with cows fed MgO in diets containing 0.35 to 0.4% Mg, suggesting a similar but possibly lower absorption of Mg from CaMg(CO 3 ) 2 (which is 1 of the 2 components of our BLN treatments). However, this needs to be further evaluated with in vivo experiments where other indicators such as plasma concentration of Mg can be assessed.…”
Section: Ruminal Ph and Mg Solubilitysupporting
confidence: 84%
“…Recent research suggests that CaMg(CO 3 ) 2 may be a useful source of Mg for dairy cows as indicated by production parameters and blood Mg concentration of cows (Leno et al, 2017), but its effects on ruminal fermentation are unknown. Additionally, to the best of our knowledge, CaMg(OH) 4 has not been evaluated yet as a source of Mg for dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Less information is available about the effect of magnesium oxide on performance of dairy cows (Emery et al, 1965;Xin et al, 1989;Tebbe et al, 2018) and feed intake (Beede, 2017). The effectiveness of magnesium oxide sources in raising rumen pH and fostering improvements in milk yield and milk fat has been reported to differ across sources (Schaefer et al, 1982;Leno et al, 2017;Tebbe et al, 2018), and Lough et al (1990) showed that magnesium oxide was more effective than magnesium chelate in promoting increases in DMI, milk yield, and milk fat content. The acid-neutralizing capacity of sodium bicarbonate and especially magnesium oxide depends on several physical and chemical characteristics, which lead to different rates of solubilization in the rumen fluid (Le Ruyet and Tucker, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Because MgO is an expensive Mg source, other sources, such as calcium-magnesium carbonate [CaMg(CO 3 ) 2 ] and calcium-magnesium hydroxide [CaMg(OH) 4 ], have been studied in relation to ruminal fermentation and dairy cow performance as potential alternatives to MgO (May et al, 2009;Leno et al, 2017;Arce-Cordero et al, 2020, 2021. Calcium-magnesium carbonate is a potential source for replacing MgO with no differences in dairy cow performance (Leno et al, 2017) and in vitro ruminal nutrient digestibility (Arce-Cordero et al, 2020).…”
Section: Effects Of Replacing Magnesium Oxide With Calcium-magnesium ...mentioning
confidence: 99%